Salicylic acid treatment induced change in the morphological, chlorophyll content, and phytochemical traits in two rice genotypes - YAYUK MULYATI; SITI ZUBAIDAH; AFIFUDDIN LATIF ADIREDJO; MOCHAMMAD ROFIQ; NURUL JADID; TRIONO BAGUS SAPUTRO; ISNAWATI ISNAWATI; FITRIARI I. MUHAIMIN; FARAPTI FARAPTI; GADIS MEINAR SARI (Society for Indonesian Biodiversity, 2025)
Abstract. Mulyati Y, Zubaidah S, Adiredjo AL, Rofiq M, Jadid N, Saputro TB, Isnawati, Muhaimin FI, Farapti, Sari GM. 2025. Salicylic acid treatment induced change in the morphological traits and the content of chlorophylls and endogenous salicylic acid in two rice genotypes. Biodiversitas 26: 778-788. Salicylic acid (SA) plays a crucial role in rice plant resistance. At the same time, the elicitation mechanisms of its induction are not well understood. The exploration of rice's endogenous SA during the vegetative and generative phases in response to SA elicitation is a new area of study. Similarly, the correlation between SA and rice resistance characteristics is a fresh perspective that this research aims to address. The study focuses on the effect of exogenous salicylic acid (SA) elicitation on plant height, the content of chlorophyll a, b and total chlorophyll, endogenous SA, and the number of productive shoots and filled grains) characters in two rice genotypes, namely genotype A (Situbagendit×Cibogo3) and genotype B (Situbagendit×Ciherang8). SA at concentration 0-2.5 mg L?¹ was applied to the in vitro shoot culture of the rice varieties. The results showed that genotype B had significant content of chlorophyll a, total chlorophyll, endogenous SA content (generative phase), number of productive shoots, and filled rice grains compared to genotype A. SA concentration of 2 mg L?¹ was proven to be the optimal dose that could maximize the resistance and productivity characters of genotype B. Conversely, higher or lower concentrations tended to produce less significant or negative effects. A positive correlation between endogenous SA content and the number of productive shoots was found in genotype B. This study revealed the importance of genetic factors and elicitor concentration in improving rice resistance traits that affect productivity. These findings have practical implications, as they contribute to the development of superior rice cultivars that can support sustainable food security, offering hope for the future of agriculture.